Adjectives, number and interfaces : why languages vary - Bouchard, Denis (North-Holland linguistic series, 2002)
A study of why languages vary the way they do in the domain of adjectival modification in French as contrasted with other Indo-European languages (English, Celtic, Walloon, Romanian, Italian). Rejecting previous well-known analyses in terms of syntactic movement to various functional heads, the author proposes a model in which external properties of interfaces are the foundations from which the variation is derived. Limiting severely the technical apparatus of syntax, the author argues that the properties of number at the interfaces are shown to provide a simple and precise solution for longstanding problems of compositionality raised by adjectival modification. There is also a unified analysis of the many other properties involved. The model provides a principled explanation of the variation concerning nominals without determiners (bare NPs) and determiners without nominals (clitics).